2010
DOI: 10.1055/s-0030-1261945
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas Involving the Sphenoid Wing Outcome after Microsurgical Treatment – A Clinical Review of 73 Cases

Abstract: The result of this study affirms the safety of microsurgical treatment strategies, so that sufficient tumor control can be achieved with minimal morbidity and satisfying functional results in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 39 publications
3
39
1
Order By: Relevance
“…The improved percentage of postoperative KPS in patients aged <60 years was higher than that in patients aged ≥60, but their difference was also not statistically significant. As some studies showed [6,7], impairment of vision was the most common symptom followed by headache of SWMs in our data. After operation, the two symptoms improved in some patients.…”
Section: General Variablessupporting
confidence: 72%
“…The improved percentage of postoperative KPS in patients aged <60 years was higher than that in patients aged ≥60, but their difference was also not statistically significant. As some studies showed [6,7], impairment of vision was the most common symptom followed by headache of SWMs in our data. After operation, the two symptoms improved in some patients.…”
Section: General Variablessupporting
confidence: 72%
“…Early postoperative conformational radiotherapy for SOM with incomplete resection was previously reported [1,29]. For grade II and III, additional irradiation is mandatory [30].…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%
“…In a current series of 73 sphenoid ridge meningiomas (Honig et al 2010), rates of perioperative morbidity and mortality were 7% and 3%, respectively, with 11 patients (15%) developing tumour recurrence (mean follow-up 29.8 months). In another series of 117 foramen magnum meningiomas, perioperative mortality was 1.8%, recurrence rate among the 93 followed up patients was calculated for 1.1% (Wu et al 2009).…”
Section: Outcomementioning
confidence: 77%
“…The least includes meningiomas arising from either the medial, clinoidal, alar or outer, temporal/pterional portion of the sphenoid ridge (30.1%, 6.9% and 16% of all meningiomas involving the sphenoid ridge, respectively) (Honig et al 2010;Mendenhall et al 2004;Condra et al 1997;Rockhill et al 2007). …”
Section: Locationsmentioning
confidence: 99%